A molecular dynamics study of lithium grain boundary intercalation in graphite. (June 2015) - Shumeyko, Christopher M.; Webb, Edmund B.
Abstract : Lithium-ion diffusion rates in graphitic battery anodes have been shown to vary greatly in experiments, with numerous hypotheses to explain this behavior. Here, we model several grain boundaries using molecular dynamics and quantify intercalation from the free surface. A significant variation in intercalation rates is revealed as dictated by local bond structure where the grain boundary intersects the free surface. Data presented may help explain dramatic differences in diffusion rates and permit more accurate predictions of lithium-ion battery performance.